Pemeriksaan HCG (Human Chorionic Gonadotropin) Dengan Metode Latex Dan Metode Strip Test Untuk Deteksi Kehamilan - Herin Tixa Dewanti; Eka Nurdianty Anwar (Gayaku Publisher, 2022)
HCG (Human Chorionic Gonadotropin) is a hormone produced by young placental tissue and secreted by urine in the event of abnormal proliferation of chorionic epithelial tissue. The presence of urinary HCG can be used for pregnancy detection. Pregnancy check can be done by latex method and strip test method. This study aims to determine the description of HCG (Human Chorionic Gonadotropin) examination with latex method and strip test method for pregnancy detection. The research used Purposive sampling technique with 25 samples of pregnant women in the first trimester. The determination of gestational age in a simple way is by counting the first day of the last menstrual period (HPHT), 3 weeks, 2 people (8%), 4 week HPHT, 4 (16%), 5 week HPHT, 3 (12%) , 6-week. HPHT was 2 people (8%), HPHT 7-8 weeks there were 6 people (24%), HPHT 9- 12 weeks there were 8 people (32%). Of the 25 samples examined using two methods namely the method of latex and the method of Strip Test, all samples tested positive pregnant (100%).